2012
DOI: 10.3171/2011.8.jns101896
|View full text |Cite
|
Sign up to set email alerts
|

The quiet revolution: retractorless surgery for complex vascular and skull base lesions

Abstract: Fixed retraction can be supplanted by dynamic retraction with surgical instruments, limiting the risk of retractor-induced tissue edema and injury. This quiet revolution has precipitated a major change in surgical techniques. Extensive dissection of arachnoidal planes, careful placement of the handheld suction device, patient positioning that enhances gravity retraction, the refinement of microsurgical instrumentation, and appropriate selection of the operative corridor all serve to obviate the need for fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 20 publications
2
72
0
3
Order By: Relevance
“…In the group with repeat imaging, 145 patients (24.3%) had mi- nor postcoiling residuals and 127 (22.1%) had significant aneurysm residual or growth. In the latter group, initial treatment with coiling resulted in complete occlusion in 68.5% (87), subtotal occlusion in 22.0% (28), and incomplete occlusion in 9.4% (12). The fact that the 68.5% of the patients with significant aneurysm residual or growth on follow-up were documented to have had complete aneurysm obliteration after initial treatment is troublesome and emphasizes the risk of recurrence of coil-treated aneurysms and the need for continued follow-up.…”
Section: Obliteration and Rebleeding Of Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the group with repeat imaging, 145 patients (24.3%) had mi- nor postcoiling residuals and 127 (22.1%) had significant aneurysm residual or growth. In the latter group, initial treatment with coiling resulted in complete occlusion in 68.5% (87), subtotal occlusion in 22.0% (28), and incomplete occlusion in 9.4% (12). The fact that the 68.5% of the patients with significant aneurysm residual or growth on follow-up were documented to have had complete aneurysm obliteration after initial treatment is troublesome and emphasizes the risk of recurrence of coil-treated aneurysms and the need for continued follow-up.…”
Section: Obliteration and Rebleeding Of Aneurysmsmentioning
confidence: 99%
“…Finally, avoiding the use of rigid retraction even for the most complex aneurysms, as was done routinely during BRAT, minimizes surgical trauma to adjacent brain tissue. 28 Although there is continued and dramatic progress in endovascular technology, there is also a price associated with the use of complex aneurysmal constructs. Early promising results with stents provide tantalizing promise of the ability to treat more complex aneurysms.…”
Section: Evolution Of Treatmentmentioning
confidence: 99%
“…Additionally, recent advances in surgical techniques including minimal retraction and retractorless aneurysm clipping are evolving to improve the long-term outcome in these patients. 16) Old age and female sex are strong predictors of poor outcome in the general population. 9) Studies discussing outcomes of aneurysmal SAH in young adults have demonstrated favorable outcomes in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…3). 1,18,19 The diagnosis is generally made radiographically and the preoperative work-up includes MRI and computed tomography. Magnetic resonance venograms can be useful to evaluate venous anatomy, dominance of transverse/sigmoid sinuses, temporal lobe draining patterns, and jugular bulb size.…”
Section: Posterior Skull Base Meningiomasmentioning
confidence: 99%
“…The introduction of microsurgical techniques, advances in neuroanesthesiology, magnetic resonance imaging (MRI), neuronavigation, injury to underlying brain. 1 Patient positioning that enhances gravity retraction, extensive dissection of arachnoid planes, the refinement of microsurgical instrumentation, appropriate selection of operative corridors, and neuronavigation have all been used to improve patient outcomes and reduce morbidities. [1][2][3][4] The key principle of skull base surgery is to deconstruct the bony skull base around the brain to create safe apertures to resect deep-seated pathologies.…”
Section: Introductionmentioning
confidence: 99%